Blockade of Mbd2 by siRNA-loaded liposomes protects mice against OVA-induced allergic airway inflammation via repressing M2 macrophage production - Wu, Guo-Rao; Zhou, Min; Wang, Yi; Zhou, Qing; Zhang, Lei; He, Long; Zhang, Shu; Yu, Qilin; Xu, Yongjian; Zhao, Jianping; Xiong, Weining; Wang, Cong-Yi (Frontiers in Immunology, 2022)
Objective: To address the role of methyl-CpG-binding domain 2 (MBD2) in the pathogenesis of asthma and its potential as a target for the asthmatic therapy. Methods: Studies were conducted in asthmatic patients and macrophage-specific Mbd2 knockout mice to dissect the role of MBD2 in asthma pathogenesis. Additionally, RNAi-based therapy with Mbd2 siRNA-loaded liposomes was conducted in an ovalbumin (OVA)-induced allergic airway inflammation mouse model. Results: Asthmatic patients and mice challenged with OVA exhibited upregulated MBD2 expression in macrophages, especially in alternatively activated (M2) macrophages. In particular, macrophage-specific knockout of Mbd2 protected mice from OVA-induced allergic airway inflammation and suppressed the M2 program. Notably, intratracheal administration of liposomes carrying Mbd2 siRNA decreased the expression of Mbd2 and prevented OVA-induced allergic airway inflammation in mice, as indicated by the attenuated airway inflammation and mucus production. Conclusions: The above data indicate that Mbd2 implicates in the pathogenesis of asthma predominantly by regulating the polarization of M2 macrophages, which supports that Mbd2 could be a viable target for treatment of asthma in clinical settings.